![image](https://tex.z-dn.net/?f=f%28x%29+%3D+%5Cfrac%7Bx%5E2+%2B+3%7D%7Bx%2B1%7D%3B%5C%5C%0Af%27%28x%29%3D%5Cfrac%7B%28x%5E2%2B3%29%27%5Ccdot%28x%2B1%29+-+%28x%5E2%2B3%29%5Ccdot%28x%2B1%29%27%7D%7B%28x%2B1%29%5E2%7D%3B%5C%5C%0Af%27%28x%29%3D%5Cfrac%7B2x%5E2%2B2x-x%5E2-3%7D%7B%28x%2B1%29%5E2%7D%3D%5Cfrac%7Bx%5E2%2B2x-3%7D%7B%28x%2B1%29%5E2%7D%3B%5C%5C%0Af%27%28x%29%3D0%2C+%3D%3E+%5Cfrac%7Bx%5E2%2B2x-3%7D%7B%28x%2B1%29%5E2%7D%3D0%3B%5C%5C%0A+%5Cleft+%5C%7B+%7B%7Bx%5E2%2B2x-3%3D0%7D+%5Catop+%7Bx+%5Cneq+-1%7D%7D+%5Cright.+%5C%5C%0A+x_%7B1%7D%3D1%3B%5C+x_2%3D-3%3B%5C%5C+)
\frac{x^2+2x-3}{(x+1)^2}=0;\\
\left \{ {{x^2+2x-3=0} \atop {x \neq -1}} \right. \\
x_{1}=1;\ x_2=-3;\\ " alt="f(x) = \frac{x^2 + 3}{x+1};\\
f'(x)=\frac{(x^2+3)'\cdot(x+1) - (x^2+3)\cdot(x+1)'}{(x+1)^2};\\
f'(x)=\frac{2x^2+2x-x^2-3}{(x+1)^2}=\frac{x^2+2x-3}{(x+1)^2};\\
f'(x)=0, => \frac{x^2+2x-3}{(x+1)^2}=0;\\
\left \{ {{x^2+2x-3=0} \atop {x \neq -1}} \right. \\
x_{1}=1;\ x_2=-3;\\ " align="absmiddle" class="latex-formula">
Ответ: точки
![x=-3,\ x=-1,\ x=1 x=-3,\ x=-1,\ x=1](https://tex.z-dn.net/?f=x%3D-3%2C%5C+x%3D-1%2C%5C+x%3D1)
являются экстремумами.